TCD monitoring of cerebral blood flow: Spremljanje pretoka v možganskih arterijah s TCD - Tetičkovič, Erih; Menih, Marija; Magdič, Jožef (Acta Medico-Biotechnica, 2021)
Transcranial Doppler monitoring of intracranial blood flow during carotid endarterectomy, carotid angioplasty with stenting, surgical management of intracranial aneurysms, coronary artery bypass grafting, and thrombolysis of middle cerebral artery (MCA) occlusions is important because it enables recording of the flow in the MCA in real time. An adequate blood flow through the MCA during carotid endarterectomy allows for selective use of an intraluminal shunt (or the decision to operate without it) and timely identification of cerebral hyperperfusion, vasospasm, hypoperfusion, and cerebral microembolisms as well as recanalization of the cerebral artery, thus minimizing postoperative neurologic complications such as stroke or cognitive dysfunction.
Keywords: Transcranial Doppler ultrasonography; carotid endarterectomy; carotid angioplasty with stenting; ruptured aneurysms in subarachnoid hemorrhage; coronary artery bypass grafting; thrombolysis